A Colonial Cacicazgo: the Mendozas of Seventeenth-Century Tepexí de la Seda - Hoekstra, Rik (European Review of Latin American and Caribbean Studies, 2010)
The cacicazgo, or indigenous lordship, was a pivotal institution in colonial Mexican Indian pueblos. Caciques, or Indian nobles, played a role, both in the largely indigenous world of the pueblo and in the regional economy that was dominated by Spaniards. This subject of this essay is the analysis of the evolution and daily operation and of a cacicazgo from the Indian settlement of Tepexí de la Seda near the city of Puebla de los Ángeles and the life of its caciques in the sixteenth and seventeenth centuries. In the sixteenth century the cacicazgo was in upheaval because of discord between the cacicazgos and their dependent Indians. A number of long-running accounts from the 1620s record in detail the daily operations of the cacicazgo of Doña Ana de Santa Bárbara of the Mendoza family, thus illustrating how caciques negotiated their positions and coped with their lives and the changes in it.   Resumen: Un cacicazgo colonial: los Mendoza de Tepexí de la Seda en el siglo 17 El cacicazgo, o señorío indígena, fue una institución fundamental en los pueblos indios de México colonial. Los caciques, o nobles indígenas, desempeñaron un papel tanto en el mundo en gran parte indígena del pueblo y en la economía regional dominada entonces por los españoles. El tema de este ensayo es el análisis de la evolución y operación cotidianas de un cacicazgo del asentamiento indígena de Tepexí de la Seda cerca de la ciudad de Puebla de los Ángeles y la vida de sus caciques en los siglos 16 y 17. En el siglo 16, el cacicazgo vivió tiempos convulsos debido a los conflictos entre los caciques y sus dependientes indios. Varias extensas cuentas de los años veinte del siglo 17 registran en detalle las operaciones diarias del cacicazgo de doña Ana de Santa Bárbara, de la familia Mendoza, mostrando así cómo negociaban los caciques sus posiciones y se adaptaban a los cambios en sus vidas.